Cross-lingual plagiarism detection techniques for English-Hindi language pairs. (19th May 2019) - Agarwal, Basant
Abstract: Plagiarism is defined as stealing of another author's language, thoughts, or ideas as one's own original work. Most of the work in the literature has been emphasized on monolingual plagiarism detection. Given text in two different languages, the objective of Cross-Lingual Plagiarism Detection (CLPD) model is to determine if the text in one language is plagiarized with the text written in another language. The cross-lingual plagiarism detection is mainly an unexplored area and is very important to improve the ethical practice, academic integrity and honesty in academics. The problem of CLPD has emerged as very important yet difficult problem because it is very easy to steal the content of a document written in another language through translation softwares. In this paper, we present different cross-language plagiarism detection approaches in context of Indian languages pairs such as Hindi-English, English-Hindi language pairs. The research in cross-language plagiarism detection is very limited but has opened up opportunities due to development in recent advancement in distributed word representation techniques in monolingual and bi-lingual context.